INDEKS PEMBANGUNAN MANUSIA (IPM) DI WILAYAH INDONESIA TIMUR - Wardhana, Adhitya; Kharisma, Bayu; Risti, Silvia (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.12.TAHUN.2022, 2022)
This research analyze the influence of government spending in the education, health and information technology sectors on the increase in HDI in eastern Indonesia. The research model used is the generalized least square model in the data panel analysis method in eastern Indonesia in 2015-2020. This research study provides results in the ratio of education and health expenditure to PDRB, internet users and PDRB per capita the previous year significantly affect hdi in eastern Indonesia. Research studies explain that PDRB per capita the previous year is the variable that most affects the Human Development Index (HDI).